2016
DOI: 10.3122/jabfm.2016.02.150214
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Program to Reduce Functional Decline in Frail Elderly People: A Cluster Controlled Trial

Abstract: Background:The increasing number of community-dwelling frail elderly people poses a challenge to general practice. We evaluated the effectiveness of a general practitioner-led extensive, multicomponent program integrating cure, care, and welfare for the prevention of functional decline.Methods: We performed a cluster controlled trial in 12 general practices in Nijmegen, the Netherlands. Community-dwelling frail elderly people aged >70 years were identified with the EASY-Care twostep older persons screening ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 38 publications
1
82
0
2
Order By: Relevance
“…However, some of the intervention components and context factors might be similar in other cases and given the detailed explanations of the setting provided here, we believe our results to hold much learning potential for other organisations currently implementing or planning to implement integrated care interventions for geriatric and other chronic conditions. This is especially relevant given the fact that many studies on integrated geriatric care stem from the Dutch context and insights from other settings are still relatively sparse [2123]. …”
Section: Discussionmentioning
confidence: 99%
“…However, some of the intervention components and context factors might be similar in other cases and given the detailed explanations of the setting provided here, we believe our results to hold much learning potential for other organisations currently implementing or planning to implement integrated care interventions for geriatric and other chronic conditions. This is especially relevant given the fact that many studies on integrated geriatric care stem from the Dutch context and insights from other settings are still relatively sparse [2123]. …”
Section: Discussionmentioning
confidence: 99%
“…Information provided about the exact content of the instrument varied between CGAs. For five CGA instruments, the content of the CGA was available in (the appendix of) the original study or in a study cited in the original study (Buurman et al, ; Buurman, Parlevliet, van Deelen, de Haan, & de Rooij, ; Fleischer et al, ; Ruikes et al, , ; Stijnen, Duimel‐Peeters, et al, ; Suijker et al, , ). For the other CGAs, the original study did not provide or only partially provided the exact content of the CGA nor referred to other papers describing this information.…”
Section: Resultsmentioning
confidence: 99%
“…Three CGA instruments were tested for their validity and reliability (De Stampa et al, ; Ruikes et al, , ; Van Hout et al, ; Vedel et al, ). For four CGAs, it was explicitly indicated that the instrument was tested for its feasibility (Daniels et al, ; Metzelthin, van Rossum, de Witte, Hendriks, & Kempen, ; Metzelthin et al, ; Ruikes et al, , ; Stijnen, Duimel‐Peeters, et al, ; Suijker et al, , ). For nine CGAs, the average duration of conducting the assessment was described, which ranged from 30 min to 3 hr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second, from the Netherlands, found that a specific team-based intervention for frail elderly in their homes did not lead to improvements in overall function or mortality. 5 For our thought piece this month, Howard et al 6 note that many practices undergoing transformation are using different terminology than are associated nationally with the PCMH initiative. These differences suggest future directions or areas that are inadequately addressed through the classic PCMH model.…”
mentioning
confidence: 99%